The value of dental morphology in the archaeological context: example of a Portuguese population from the late 19th and early 20th centuries - Marado, Luís Miguel (2012)
The observation of dental non-metric characters used in the Arizona State University Dental Anthropology System (among others) is of major interest in the study of past populations. Dental morphological traits are genetically determined, and dependent of a small and stable part of the genome; their development seems unaffected by the uterine environment and their evolution is slow, probably independent of natural selection. The relative frequency of dental traits is a testimony to the biological distances between populations. The study of the inferior dentition in a late XIXth/early XXth century sample deceased in Oporto, Portugal, is the example of a statistically simple approach to the biological comparison between populations, using the ASUDAS (Turner et al. 1991), mainly, but also a trait proposed by Weets (2009). The comparisons with international samples denoted biological relatedness with European and, to a lesser extent, North African populations. The Iberian samples also suggest a close relationship with those populations. The use of the ASUDAS to the study of teeth from archaeological contexts is important. A greater collection of data will be used in the determination of the population history of the Iberian Peninsula. Important questions, relative to cultural influence/colonization may then be closer to resolution.